Aplicación web de gestión para las membresías e inventario de equipos para Sam-Gym Fitness Center - Villarreal Ortiz, Marco Sebastian (2024)
This thesis describes the development of a web application for the efficient management of memberships and inventory at SAM-GYM Fitness Center, a gym located in Ibarra. The web application was created with the aim of modernizing and automating the processes of this sports center, improving operational efficiency and customer experience. A Model-View-Controller (MVC) architecture was used, employing React.js for the user interface, NestJS for the business logic, and MySQL as the relational database. The development methodology was Extreme Programming (XP), with incremental deliveries and continuous testing. The application allows registering clients and associating them with configurable memberships, managing the inventory of equipment and products by categories and suppliers, making sales, and generating reports for income, expenses, and profit/loss summaries. Intuitive interfaces were designed to facilitate these tasks. Functional black-box testing demonstrated that the application meets the established requirements and provides a satisfactory user experience. The solution leverages leading technologies to optimize gym management, driving growth and competitiveness in the market. To enhance the quality of this document, artificial intelligence (AI) was employed to refine the writing and coherence of the text. This technology was crucial in ensuring that the exposition of ideas and the document's structure were clear and consistent throughout the academic work. Through advanced natural language processing (NLP) techniques, the expression of complex concepts was optimized, guaranteeing a high-level academic presentation. This approach not only facilitated readers' comprehension of the content but also underscored the author's ability to integrate technological innovations within the academic realm.